2009
DOI: 10.2320/matertrans.mbw200804
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Martensitic Transformation in Sensitized SUS304 Austenitic Stainless Steel at Cryogenic Temperature

Abstract: We have investigated martensitic transformation behavior in a sensitized SUS304 austenitic stainless steel to know the stability of the austenitic phase at cryogenic temperatures. We found that the sensitized specimen exhibits an isothermal martensitic transformation when the specimen is held in the temperature range between 60 and 260 K. The time-temperature-transformation (TTT) diagram corresponding to the formation of 0.5 vol% of 0 -martensite shows a double-C curve with two noses located at about 100 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…7 Time-dependent growth of lath martensite was followed in-situ by microscopical investigations in Ref. [11][12][13][14][15] and it was observed to induce time-dependent (autocatalytic) nucleation of lath martensite. 12,13,15 After initial nucleation and growth, autocatalytic nucleation is responsible for an acceleration of the transformation.…”
Section: Introductionmentioning
confidence: 99%
“…7 Time-dependent growth of lath martensite was followed in-situ by microscopical investigations in Ref. [11][12][13][14][15] and it was observed to induce time-dependent (autocatalytic) nucleation of lath martensite. 12,13,15 After initial nucleation and growth, autocatalytic nucleation is responsible for an acceleration of the transformation.…”
Section: Introductionmentioning
confidence: 99%
“…At magnetic saturation, the magnetisation of paramagnetic phases (i.e. c austenite 44 and e martensite, 45 when present) is several orders of magnitude smaller than the magnetisation of ferromagnetic phases (i.e. a´ martensite).…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6][7] This effect can be induced by deformation and also by cooling to a low temperature (2195uC). 8,9 Recent work by the authors has reported that a 321 grade stainless steel contained ferrite in the solution heat treated condition and that the amount of ferrite increased with aging. 10 The transformation of c to a or a9 is of industrial relevance when it is considered that a brittle/ductile transition could be introduced and an increase in volume is incurred, which is generally quoted as y4% for a complete transformation.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of α' is usually associated with deformation and it is known that martensite can form in the 300 series of stainless steel during deformation at temperatures well above the marteniste start temperature [4][5][6][7]. This effect can be induced by deformation and also by cooling to a low temperature (-195°C) [8,9]. Recent work by the authors has reported that a 321 grade stainless steel contained ferrite in the solution heat treated condition and that the amount of ferrite increased with ageing [10].…”
Section: Introductionmentioning
confidence: 99%